2019
DOI: 10.3382/ps/pez458
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of sire contribution and breed-of-origin of alleles in a three-way crossbred broiler dataset

Abstract: Broiler breeding programs rely on crossbreeding. With genomic selection, widespread use of crossbred performance in breeding programs comes within reach. Commercial crossbreds, however, may have unknown pedigrees and their genomes may include DNA from 2 to 4 different breeds. Our aim was, for a broiler dataset with a limited number of sires having both purebred and crossbred offspring generated using natural mating, to rapidly derive parentage, assess the distribution of the sire contribution to the offspring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…The BOA program of Vandenplas et al [ 13 ] showed a higher proportion of alleles in real genotypes that could not be assigned than in most of the simulated scenarios that they studied. Application of their program on three-way pig data assigned 95.2% of the alleles to breed of origin [ 10 ], but on chicken data 91.8% of the alleles could be assigned to breed of origin for the three-way crosses and 96.9% for the F1 crosses [ 27 ]. Our preliminary results of the application of AllOr on real genotypes of crossbred dairy cows are promising with more than 99% of the alleles assigned to breed of origin (personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…The BOA program of Vandenplas et al [ 13 ] showed a higher proportion of alleles in real genotypes that could not be assigned than in most of the simulated scenarios that they studied. Application of their program on three-way pig data assigned 95.2% of the alleles to breed of origin [ 10 ], but on chicken data 91.8% of the alleles could be assigned to breed of origin for the three-way crosses and 96.9% for the F1 crosses [ 27 ]. Our preliminary results of the application of AllOr on real genotypes of crossbred dairy cows are promising with more than 99% of the alleles assigned to breed of origin (personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…The number of multiplication steps that occur in the purebred lines prior to crossing has no effect on the assignment of line-origin, because it only depends on the composition of the crossbred genome. In studies using real data, 95.2% of the alleles of three-way crossbreds pigs [ 45 ] and 91.1% of the alleles of three-way crossbred broilers [ 46 ] could be assigned to one of the lines using this method. The lower percentage in broilers was probably because the number of purebred genotypes available was small for one line [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In studies using real data, 95.2% of the alleles of three-way crossbreds pigs [ 45 ] and 91.1% of the alleles of three-way crossbred broilers [ 46 ] could be assigned to one of the lines using this method. The lower percentage in broilers was probably because the number of purebred genotypes available was small for one line [ 46 ]. Since the correct line origin is not known in real data, the accuracy of assigning the line-origin was investigated in a simulation study, which showed that the line-origin of an allele could be correctly assigned for 94.3 to 97.2% of the alleles in three-way crossbreds, with a higher percentage when the lines were more distantly related [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study reuses data from a broiler three-way cross experiment that was previously analysed [13][14][15][16]. The main advantages of this dataset are that (1) all the phenotyped animals are genotyped, (2) the pedigree and the observed breed composition of all the crossbred animals were previously derived by Calus et al [13], and (3) the three purebred lines have been shown to be distantly related [15,16]. Furthermore, Duenk et al [14] analysed the same dataset using models based on the breed-oforigin (BOA) of alleles, which enabled us to compare our results to those obtained with that model.…”
Section: Methodsmentioning
confidence: 99%